The Determinants of Unemployment in Sudan: A Co-integration and Error Correction Model Analysis (1981-2011) - Mustafa, Mohammed Elhaj (Gezira Journal of Economic and Social Sciences, 2013)
The main purpose of this paper is to investigate the determinants of unemployment in Sudan using time series data over the period 1981 - 2011. Co integration and VECM techniques were applied to carry out the investigation. The overall econometric analysis showed that the variables under consideration have co integrating relationships implying that they have long-run relationships. The results of VECM estimation suggests that growth in GDP, the interaction between FDI and average years of schooling play a positive role in unemployment reduction in the long-run, while in the short-run this impact has been reversed. Inflation is found to have a positive impact on unemployment mitigation in the short run and, therefore, provides strong evidence to be added to the already existing large body of literature validating the existence of short-run Phillips Curve. On the other hand, the estimated results suggest that economic openness and oil production contribute negatively to unemployment reduction in the short as well as in the long run. Also the findings of the study confirmed the pivotal role for privatization policy in combating unemployment.